Abdominal incisions–vertical or transverse?. Issue 704 (June 1984) - Ellis, H.; Coleridge-Smith, P. D.; Joyce, A. D.
Abstract : Two-hundred and nine patients were entered into a prospective, randomized trial in order to determine whether a vertical or transverse abdominal incision is the more satisfactory in producing sound wounds. Ninety-six patients were randomized between paramedian and transverse incisions, and followed up for at least 1 year. No significant difference in the incidence of wound failure could be shown between 46 paramedian and 50 transverse incisions. Those patients who were considered to require a vertical incision were randomized between median and paramedian incisions. No significant difference in wound failure rates between 39 median and 40 paramedian incisions could be demonstrated. No advantage or disadvantage of a transverse over a vertical abdominal incision or of a paramedian over a median incision could be shown in this study.